Leaders' Views on the Implications of Digital Technologies for the Future of Physical Therapy. - Xi, Jason; Somal, Harneet; Eskic, Luka; Patel, Tanha; Mohamed, Saara; Liolios, Nicole; Walton, David M.; Shaw, James (Physiotherapy Canada, 2026)
Purpose: This study explores Canadian physical therapy (PT) leaders' knowledge of digital technologies and examines their beliefs about the ways in which emerging technologies will shape PT practice in the future. Method: We recruited 11 physical therapists with leadership roles at universities, commercial technology vendors, clinics, and regulatory bodies. We conducted semi-structured interviews and then analyzed them using the DEPICT model. Results: Participants were most knowledgeable in the use of telerehabilitation in PT practice. Participants believed there were opportunities for and challenges with the further integration of technology into the profession. Participants believed technology is increasingly pressuring the profession to change. A subset of participants believed the idea of professional evolution and maturity should serve as a lens through which the profession views the implications and further integration of technology into physical therapy care. Last, we found that access to care was a focal point for discussion of the integration of technology into the profession. Conclusions: The findings underscore the importance of further research and policy development regarding the maturity of the PT profession, with a particular focus on the interconnected issues of digital technology and access to care. Lay Summary: Digital technologies are changing the way physical therapists deliver care. Tools such as virtual rehabilitation (telerehabilitation), robotics, wearable devices, and self-management apps are becoming more common in practice. These technologies offer potential benefits, including greater access to care for people living in rural or remote areas, more personalized treatment options, and new ways for patients to stay engaged in their rehabilitation. At the same time, they bring challenges, such as privacy concerns, unequal access to devices or internet, and questions about how technology may affect the human connection between patients and therapists. To better understand these issues, we interviewed Canadian leaders in physical therapy from academic, clinical, policy, and technology settings. Leaders recognized both the opportunities and the risks of digital health tools and emphasized the need to develop hybrid models of care that combine digital and in-person approaches. They also highlighted the importance of ensuring that all patients – especially those who are older, have limited resources, or live in under-served areas – can benefit from these innovations. Overall, our findings suggest that the future of physical therapy will depend on thoughtful, evidence-based integration of digital technologies while maintaining the core values of patient-centred care.